Influence of Er,Cr: YSGG laser on bond strength of self-adhesive resin cement - Bandeca, Matheus Coelho [UNESP]; Pinto, Shelon Cristina Souza [UNESP]; Calixto, Luiz Rafael [UNESP]; Saad, José Roberto Cury [UNESP]; Barros, Érico Luiz Damasceno; Shelb, Amr (ABM, ABC, ABPol, 2012)
The purpose of this study was to investigate the bond strength of fiber post previously laser treated root canals. Forty single-rooted bovine teeth were endodontically treated, randomly and equally divided into two main groups according to the type of pretreatment: G1: 2.5% NaOCl (control group); and G2: Er,Cr:YSGG laser. Each group was further subdivided into 2 groups based on the category of adhesive systems/ luting materials used: a: an etch-and-rinse resin cement (Single Bond/RelyX ARC; 3M ESPE), and b: a self-adhesive resin cement (Rely X Unicem; 3M ESPE). Three 1.5 mm thick slabs were obtained per root and the push-out test was performed at a crosshead speed of 0.5 mm/min until post dislodgement occurred. Data were analyzed by ANOVA and post-hoc Tukey's test at a pre-set alpha of 0.05. Analysis of variance showed no statistically significant difference (p > 0.05) among the groups G1a (25.44 ± 2.35) and G1b (23.62 ± 3.48), G2a (11.77 ± 2.67) and G2b (9.93 ± 3.37). Fractures were observed at the interface between the dentin and the resin in all groups. The Er,Cr:YSGG laser irradiation did not influence on the bond strength of the resin cements and the etch-and-rinse resin cement had better results on bond strength than self-adhesive resin cement.
Keywords: Er,Cr:YSGG laser; root canal dentin; push-out bond strength; fiber post; resin cement